PENGGUNAAN MODEL TEAMS GAMES TOURNAMENT (TGT) BERBANTUAN MEDIA PERMAINAN ULAR TANGGA UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA KELAS V SDN 13 KAPALO KOTO KOTA PADANG - Dea Sinta Maharani; Junaidi Indrawadi; Ulil Amri (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This research is motivated by the results of observations made in class VB at SDN 13 Kapalo Koto which shows that student learning activities are still low. This is due to the Covid-19 pandemic that hit the world so that the learning process is carried out online, the online learning process cannot stimulate students to carry out learning activities so that when studying in class students' learning activities are low. This study aims to increase student learning activities using the Cooperative learning model of the Teams Games Tournament (TGT) type assisted by the snake and ladder game media. The type of research used is classroom action research which consists of two cycles with 4 stages, namely planning, implementation, observation and reflection. The subjects of this study were students of class VB with a total of 31 students. The data collection method used is observation. The results showed that the average percentage of student learning activities classically increased. This can be seen from the results of observations of student learning activities in cycle 1 is 64.52% and cycle 2 is 85.28%. Based on the results of this study, it can be concluded that the use of the TGT type cooperative model with the help of snakes and ladders game media can improve student learning activities.